Regulating fintech: Objectives, principles, and practices - Marlene Amstad (Asian Development Bank Institute (ADBI), 2019)
This paper starts by revisiting the true definition of money and identifies that electronic money is not a new concept. It explains the spectrum of money in the context of the past, present, and future and argues that technology can only enhance the way we deal with money and will never change the nature of money. The prospect of digital currency relies on innovation capacity, not only on central banks. The discussions propose that a central bank is similar to a welfare society, and demand for digitalization has always been present due to problems such as nano units and coverage. The author recommends tackling each digitization challenge sequentially and with a logical approach.
Keywords: G15; F65; O16; 330; fintech; financial technology; digital currency